Petroliam Nasional Berhad (PETRONAS) / Akmal Fahmi Mohammad Zamri - Mohammad Zamri, Akmal Fahmi (Faculty of Business and Management, 2023)
This executive summary offers an overview of the internship report completed at Petroliam Nasional Berhad (PETRONAS) between March 1st to August 15th, 2023. The purpose of this report is to summarize the major findings, experiences, and recommendations gained during the internship programme. Tasks executed throughout my internship journey advanced my understanding of the department's role in fulfilment of the company's goals and offered exposure to various facets of the industry. Furthermore, the internship allowed me to gain insight and acquire knowledge from experienced professionals within the organization. Interactions with supervisors and teammates on a regular basis opens more doors for the exchange of ideas and knowledge transferring information. The healthy work environment encouraged personal and professional development, allowing for the enhancement of critical skills such as effective communication, teamwork, and problem-solving. Throughout the journey, I have worked on tasks related to the Business Requirement Document, which identifies current process pain points and compares them to as-is and to-be processes. I also helped with the review and interpretation of the Business Value Realization (BVR) by working with business users to calculate the quantitative value and identify the qualitative attributes. Other responsibilities included assisting in the creation and preparation of a P4R FY2023 deck, which includes a proposed timeline and budget for registered and unregistered projects in FY2023, as well as the creation and preparation of the budget transfer request form for current-year unfunded projects. A SWOT analysis is being constructed based on the company, and several recommendations have been identified based on observations and experiences gained during the internship to further improve PETRONAS' operations and efficiency. These include process improvements, technology implementation, strategic initiatives, and so on [details of recommendations are embedded in a specific section in this report]. In its entirety, the internship at Petroliam Nasional Berhad was a rewarding experience that provided valuable insights into the industry as well as the internal operations of the organization. Being able to apply theoretical knowledge in a real-world environment has improved professional skills and aided in personal development.